Increasing 'ease of sliding' also increases friction: when is a lubricant effective?. (2nd March 2016) - Annunziata, M A; Baldassarri, A; Dalton, F; Petri, A; Pontuale, G
Abstract: We investigate experimentally the effective Coulomb friction exerted by a granular medium on a shearing plate, varying the medium depth. The plate is driven by a spring connected to a motor turning at a constant speed and, depending on the system configuration, performs continuous sliding or stick and slip in different proportions. We introduce an order parameter which discriminates between the different regimes expressing the fraction of time spent in slipping. At low driving speed, starting from zero layers of interstitial granular material, the average friction coefficient decreases when a few layers are added, while the order parameter stays close to zero. By further increasing the granular depth, the friction undergoes a sudden increase but the order parameter does not change notably. At an intermediate driving speed, however, both the friction and the order parameter undergo a sudden increase, which for the order parameter amounts to several orders of magnitude, indicating that the plate is more braked but nevertheless keeps sliding more easily. For medium-high driving speeds, full sliding is obtained for only one layer of interstitial matter, where friction has a minimum, and is maintained for all increasing depths while friction increases. These observations show that the ease of slipping is not determined by friction alone, rather by the highly complex interplay between driving velocity, friction, and the depth of the medium.